Regulating Access and Protecting Traditional Health Knowledge through Intellectual Property Rights? Issues from a Holistic Health Systems Perspective. (November 2018) - Priya, Ritu; Kurian, Chris M.
Traditional Health Knowledge (THK) has been a resource for modern pharmacology and the pharma-ceutical industry since its inception. Until the 2000s, there was little obligation to acknowledge the use of THK by the pharmaceutical industry. Now, with the intellectual property regime becoming a prominent mode of regulating use of pharmaceutical inventions and innovations, and attempts by the pharmaceutical industry to patent products based on THK, rights of THK holders are being fore-grounded. The World Intellectual Property Organization (WIPO) is seeking to protect the rights of THK holders through international legal instruments under the Intellectual Property Rights (IPR) framework. This article discusses dilemmas arising from this attempt at bringing together two diverse knowledge frameworks. It draws upon existing literature on the nature of THK and upon the debates of the WIPO's Inter-Governmental Committee on Genetic Resources, Traditional Knowledge and Traditional Cultural Expression (WIPO-IGC), and analyses them from the standpoint of a holistic health systems approach (HHSA) in an era of Sustainable Development Goals (SDGs). The approach leads to the conclusion that deliberations and promulgations of the WIPO-IGC will have long-lasting implications for the survival of diversity and context-specificity in healthcare. Therein lies the significance of thinking through the policy and legal measures to be adopted nationally and internationally.